2023
DOI: 10.3390/ijms24054910
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo, from Pathogenesis to Therapeutic Advances: State of the Art

Abstract: Vitiligo is an acquired hypopigmentation of the skin due to a progressive selective loss of melanocytes; it has a prevalence of 1–2% and appears as rounded, well-demarcated white macules. The etiopathology of the disease has not been well defined, but multiple factors contribute to melanocyte loss: metabolic abnormalities, oxidative stress, inflammation, and autoimmunity. Therefore, a convergence theory was proposed that combines all existing theories into a comprehensive one in which several mechanisms contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 128 publications
0
11
0
3
Order By: Relevance
“…However, most experts concur that vitiligo etiology and progression are significantly influenced by immune response and T-cell tolerance abnormalities ( 27 ). Furthermore, vitiligo is defined by the presence of an altered immunological balance, which is predominantly seen in an imbalance between the cytokines expressed by Treg/Th2 lymphocyte subsets (IL-4) and Th1/Th17 lymphocyte subsets (TNF-α, IFN-γ, IL-17, and IL-8) ( 28 , 29 ). Early histopathology of vitiligo lesions indicated CD8+ T cell-dominant lymphocytic infiltrated around the margin of the depigmented lesions, where the disease was most active, in a prior analysis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, most experts concur that vitiligo etiology and progression are significantly influenced by immune response and T-cell tolerance abnormalities ( 27 ). Furthermore, vitiligo is defined by the presence of an altered immunological balance, which is predominantly seen in an imbalance between the cytokines expressed by Treg/Th2 lymphocyte subsets (IL-4) and Th1/Th17 lymphocyte subsets (TNF-α, IFN-γ, IL-17, and IL-8) ( 28 , 29 ). Early histopathology of vitiligo lesions indicated CD8+ T cell-dominant lymphocytic infiltrated around the margin of the depigmented lesions, where the disease was most active, in a prior analysis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo is an autoimmune skin lesion induced by dysfunction of pigment-producing melanocytes attacked by immune cells, which ultimately ends in achromic macules and patches. In recent years, there are numerous therapeutic modalities available, that aim to stop progression and induce skin re-pigmentation [9] . It has been demonstrated that vitiligo treatment is challenging considering its complicated pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Non-segmental vitiligo clinically occupies the skin surface regardless of the dermatomes. Skin lesions in the course of vitiligo impinge on the patient's quality of life, leading to psychic discomfort, social withdrawal and stigmatization [64][65][66][67][68]. Certain exogenous and/or endogenous factors in genetically predisposed individuals lead to cellular stress within melanocytes, which promotes the migration of CD8+ T lymphocytes into the epidermis.…”
Section: Non-segmental Vitiligomentioning
confidence: 99%